Validation of a Measure of Role Overload and Gains for End-of-Life Dementia Caregivers. (21st November 2022) - Turner, Shelbie G; Epps, Fayron; Li, Minghui; Leggett, Amanda N; Hu, Mengyao
Abstract: Objectives: Caregiving stress process models suggest that heterogeneous contexts differentially contribute to caregivers' experiences of role overload and gains. End-of-life (EOL) caregivers, especially EOL dementia caregivers, facing unique challenges and care tasks, may experience role overload and gains in different ways than other caregivers. This study evaluates measurement invariance of role overload and gains between EOL caregivers and non-EOL caregivers and between EOL dementia and EOL non-dementia caregivers. Methods: We utilized role gains and overload data from 1, 859 family caregivers who participated in Round 7 of the National Study of Caregiving. We ran confirmatory factor analyses to investigate the factorial structure across all caregivers and then examined the structure's configural, metric, and scalar invariance between (a) EOL caregivers and non-EOL caregivers and (b) EOL dementia and EOL non-dementia caregivers. Results: Across the entire sample, the two-factor overload and gains model had good fit (χ  2 (19) = 121.37, p < .0001; RMSEA = .053, 90% CI = [.044, .062]; CFI = .954; TLI = .932). Tests of invariance comparing EOL caregivers to non-EOL caregivers and EOL dementia caregivers to EOL non-dementia caregivers maintained configural, metric, and partial scalar invariance. Latent mean comparisons revealed that EOL caregivers had higher role overload ( p = .0002), but no different role gains ( p = .45), than non-EOL caregivers. Likewise, EOL dementia caregivers had higher role overload ( p = .05), but no different role gains ( p = .42), than EOL non-dementia caregivers. Discussion: Results offer both a deeper theoretical understanding of end-of-life dementia caregivers' experiences of role overload and gains, and a practical tool to measure those experiences.